The road from belhaven eaudiobook A novel. - Livesey, Margot (Books on Tape, 2024)
From the New York Times best-selling author of The Flight of Gemma Hardy , a novel about a young woman whose gift of second sight complicates her coming of age in late-nineteenth-century Scotland “Bewitching and seductive.” —Rebecca Makkai, author of I Have Some Questions for You • “A treasure: a writer who understands the magic and mysteries of the human soul." —Chris Bohjalian, author of Hour of the Witch • “This book is a cold, clear, perfect lake." —Lauren Groff, author of The Vaster Wilds Growing up in the care of her grandparents on Belhaven Farm, Lizzie Craig discovers as a small child that she can see into the future. But her gift is selective—she doesn’t, for instance, see that she has an older sister who will come to join the family. As her “pictures” foretell various incidents and accidents, she begins to realize a painful truth: she may glimpse the future, but she can seldom change it. Nor can Lizzie change the feelings that come when a young man named Louis, visiting Belhaven for the harvest, begins to court her. Why have the adults around her not revealed that the touch of a hand can change everything? After following Louis to Glasgow, though, she learns the limits of his devotion. Faced with a seemingly impossible choice, she makes a terrible mistake. But her second sight may allow her a second chance. Luminous and transporting, The Road from Belhaven once again displays “the marvelous control of a writer who conjures equally well the tangible, sensory world . . . and the mysteries, stranger and wilder, that flicker at the border of that world.” — The Boston Globe